Analysis of the efficiency of technique for improving the accuracy of performing power serve in jump by skilled volleyballers - Мельник, Аліна (Slobozhanskyi Herald of Science and Sport, 2016)
Alina Mel’nik Purpose: investigating the results of replicate experiment, in which the proposed technique for improving the accuracy of performing serve was used, and carrying out a comparative analysis the corresponding results of the current and initial experiments. Material & Methods: the analysis of the video, pedagogic observations, statistical methods of processing the results. Results: the replicate experiment has been carried out. The detailed analysis of the characteristics of moving ball has been performed. The approach for estimating the accuracy of the performing serve has been proposed. The estimation of statistical validity of differences between the results of the comparative analysis of the corresponding characteristics of both experiments has been performed using criteria Student and Fisher. Conclusions: in the replicate experiment a reliable change of the characteristic, which is associated with the accuracy of performing power serve in jump, has been identified. Using techniques developed by the author in the practice of training process can be considered that it is effective.